2015
DOI: 10.5301/hipint.5000263
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of the Stryker® Trident ‘All-Poly’ Constraint Acetabular Insert: A District General Hospital Experience

Abstract: In the short to medium term, acetabular constraint offers a useful primary or revision option in patients at risk or with recurrent dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…20 Short-term results of TCLs showed an overall survival rate ranging from 86.2% to 98.8% up to 4.6 years. 7,21,25,3032 The tripolar design showed favourable outcomes with dislocation rates of 6% at 10 years. 10 A recent study with the longest follow-up demonstrated 90.6% survival rate with dislocation as the endpoint at 20 years with the TCL.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…20 Short-term results of TCLs showed an overall survival rate ranging from 86.2% to 98.8% up to 4.6 years. 7,21,25,3032 The tripolar design showed favourable outcomes with dislocation rates of 6% at 10 years. 10 A recent study with the longest follow-up demonstrated 90.6% survival rate with dislocation as the endpoint at 20 years with the TCL.…”
Section: Discussionmentioning
confidence: 96%
“…24 As a result, the optimal position and alignment of the CL are essential to avoid complications. 25 Acetabular inclination between 35° and 50° and anteversion of 0° and 20° has been suggested to maximise outcomes. 25,26 In our opinion, the proper orientation must be weighted based on the primary or revision setting and the need to revise or not the stem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as poor soft tissue quality and trochanteric insufficiency may exist in patients undergoing surgery that increase the instability of the construct and risk of dislocation. One alternative to reduce dislocation rates in such patient populations is the use of a constrained acetabular liner [ 22 ]. Constrained liners may put more stress on the fixation of the acetabular component.…”
Section: Introductionmentioning
confidence: 99%